Current studies in management information systems - GÜRDER, FİLİZ (Akademisyen Kitabevi, 2023)
Chapter 1 Migration and its Effects in Türkiye and the World - Filiz VAROL GÜRDER Chapter 2 Estimation of the Regularity of Rental Payments by Customers in the Real Estate Industry Through Data Mining - Müberra ŞEN Chapter 3 Di̇gi̇tal Li̇teraci̇es and Workplace on Start-Ups Ecosyst - Musab Talha AKPINAR Chapter 4 Customer Relationship Management in SAP SD and SAP Fiori: Processes from Inquiry to Payment - Sümeyye SÜRÜCÜ Chapter 5 Environmental Impact of Cloud Computing: An Examination on Energy Consumption and Carbon Footprint - Tolgahan Zorlu ÇELEBİ Chapter 6 Digitalisation in SMEs: The Role of Order Management and Solon Trade ERP System - Işılay OKŞAK
Keywords: Yönetim Bilişim Sistemleri; Management Information Systems; Sosyal Bilimler (SOC); Ekonomi ve İş; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Social Sciences & Humanities